The Role of the Asean Intergovernmental Commission on Human Rights (AICHR) in Protecting Human Rights Related to the Coup Conflict in Myanmar - Rizqi Hanindya Putri; Yudhan Catur Nugraha; Aristian Akbar (Budapest International Research and Critics University, 2022)
The political crisis led to a military coup conflict that forced the Myanmar people to take action. The role of the ASEAN Intergovernmental Commission on Human Rights as an integral ASEAN organization is expected to be the spearhead in the protection of human rights in ASEAN. This writing uses a normative juridical approach, is descriptive in nature, using a qualitative approach. The research uses primary and secondary legal materials. Furthermore, data analysis was carried out using qualitative analysis methods with descriptive analysis (exposure). AICHR's role in protecting human rights in the midst of the Myanmar coup conflict is also considered ineffective, this is because AICHR's ToR is still very limited. The need to revise the AICHR ToR to enlarge the scope of enforcement and protection of human rights in ASEAN, one of which is by incorporating the doctrine of Responsibility to Protect (R2P) in order to allow AICHR's steps to intervene in countries that commit human rights violations.